Extension of the code suite FLY to a multi-cell postprocessor for hydrodynamic plasma simulation codes - Sondhauss, P; Rose, S; Lee, R; Al'miev, I; Wark, J (2001)
The extension of the atomic kinetics code suite FLY to a multi-cell postprocessor for hydrodynamic plasma simulation codes, called SWARM is presented. First, the collisional radiative model on which FLY is based is reviewed as far as it corresponds to the model in SWARM, then more attention is paid to the differences. Multiple cell simulations require a more complicated algorithm to solve the radiative transfer problem, taking into account geometry and point of observation. The feedback of the radiation on the atomic state populations is taken into account in a more sophisticated escape factor model. Finally, the limitations of the model are discussed. © 2001 Elsevier Science Ltd. All rights reserved.